Hospitalizações por condições sensíveis à atenção primária nos municípios em gestão plena do sistema no Estado do Rio Grande do Sul, Brasil Hospitalization for primary care sensitive conditions in municipalities with full local health management control in Rio Grande do Sul State, Brazil - Juvenal Soares Dias-; Dóris Clarita Büttenbender; Ana Lucia Hoefel; Leonardo Lemos de Souza (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2010)
Avaliou-se a qualidade dos cuidados oferecidos nos municípios em gestão plena no Rio Grande do Sul, Brasil, por meio da taxa de internações hospitalares por condições sensíveis à atenção primária, no período de 1995 a 2005. Foram consideradas as internações hospitalares por: diabetes mellitus, insuficiência cardíaca, hipertensão arterial, doença pulmonar obstrutiva crônica e doenças imunopreveníveis em indivíduos na faixa etária de 20 a 59 anos. Verificou-se diminuição das taxas em quase todos os municípios do estado. A regressão de Poisson não mostrou tendências de diminuição das taxas após a adesão à gestão plena. Nos municípios menores, as taxas foram mais elevadas. As internações por condições sensíveis à atenção ambulatorial mostraram-se indicadores de fácil operação e de baixo custo que podem produzir conhecimentos sobre os sistemas de saúde, possibilitando a melhoria de sua qualidade. We assess the quality of care provided in the cities with full health system management, in the state of Rio Grande do Sul, Brazil, by means of the rate of hospitalizations for primary care sensitive conditions, between 1995 and 2005. The following were considered as hospitalizations for sensitive conditions: diabetes mellitus, heart failure, hypertension, chronic obstructive pulmonary disease and immunopreventive diseases in individuals aged between 20 and 59 years. Findings reveal that, beginning in 2001, there has been a reduction in rates in almost all cities. Through the Poisson regression we didn't observe a lower rates after the full health system management. Among cities with full health system management, rates of hospitalizations for ambulatory care sensitive conditions increased as the population size decreased. Hospitalizations for ambulatory care sensitive conditions were found to be low-cost, easily-operated indicators and can produce knowledge about health systems, enabling their quality improvement.